Harriet Tubman - Nichols, Catherine; Denington, Brian (New York : Scholastic, 2002)
A simple presentation of the life of Harriet Tubman, who helped over 300 slaves, including her elderly parents, to escape to freedom via the Underground Railroad.
"Cartwheel books."
G2
Keywords: Tubman, Harriet, -- 1820?-1913 -- Juvenile literature; Tubman, Harriet, -- 1820?-1913.; Slaves -- United States -- Biography -- Juvenile literature; African American women -- Biography -- Juvenile literature; African Americans -- Biography -- Juvenile literature; Underground Railroad -- Juvenile literature; Slaves; African Americans -- Biography; Women -- Biography; Underground Railroad